Sand-Fly Saliva-Leishmania-Man: The Trigger Trio - De Oliveira, Camila I.; de Carvalho, Augusto M.; Oliveira, Fabiano (Frontiers in Immunology, 2013)
Leishmaniases are worldwide diseases transmitted to the vertebrate host by the bite of an infected sand fly. Sand fly biting and parasite inoculation are accompanied by the injection of salivary molecules, whose immunomodulatory properties are actively being studied. This mini review focuses on how the interactions between sand fly saliva and the immune system may shape the outcome of infection, given the specificities of certain Leishmania-sand fly combinations; we will also cover the differences observed in these varying scenarios.